The impact of teaching using the strategy of vee in the development of religious concepts in the field of Islamic education among the ninth grade students in Jordan. - Al- Salti, Mahmoud Jamil Abdullah (Journal of Educational and Psychological Sciences, 2019)
The present study aimed to find out the impact of teaching using the(vee) strategy in the development of religious concepts in the 9th- grade students.The study adopted the semi- experimental method. The tool consisted of (test religious concepts) Of the ninth grade students at the Abu Ayyub Al- Ansari Elementary School for Boys, Directorate of Education in the Governorate of Aqaba during the academic year 2018/2019, for the Division (A) as a pilot group, consisting of (30) students, and Division B as a control group, student. Results showed (T) There were statistically significant differences between the average scores of students on the test of religious concepts due to the variable of teaching method. The control obtained average of (12.65(versus the experimental score on average of (17.25) and in favor of the vee strategy. The researcher trained the teachers on the strategy of the form (V) in the teaching of Islamic education; for their effectiveness in teaching, and recommended studies to introduce other teaching methods for comparison in achievement.
Keywords: impact; V-shape strategy; religious concepts; Islamic education topic